2023
DOI: 10.1155/2023/2252255
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 Alleviates Brain Injury by Inhibiting NLRP3-Induced Pyroptosis in a Sepsis Model

Abstract: Background. Sepsis, which could cause a systemic inflammatory response, is a life-threatening disease with a high morbidity and mortality rate. There is evidence that brain injury may be related to severe systemic infection induced by sepsis. The brain injury caused by sepsis could increase the risk of mortality in septic patients, which seriously affects the septic patient’s prognosis of survival. Although there remains a focus on sepsis research, clinical measures to prevent and treat brain injury in sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In this study, we have mainly focused on NLRP3/Caspase-1/IL-1β/ GSDMD signalling (the canonical pyroptosis pathway), that our group has been devoted to the exploration for years. 20,[29][30][31] Constantly, existing studies have initially found the role of NLRP3 in the development and progression of rosacea. [32][33][34] NLRP3 is regarded as a key member of inflammasome sensors (including NLRP1/3/4, AIM2 and pyrin), which could assemble canonical inflammasomes (formed by NOD-like receptors, Caspase-1 and ASC), leading to the maturation and release of IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have mainly focused on NLRP3/Caspase-1/IL-1β/ GSDMD signalling (the canonical pyroptosis pathway), that our group has been devoted to the exploration for years. 20,[29][30][31] Constantly, existing studies have initially found the role of NLRP3 in the development and progression of rosacea. [32][33][34] NLRP3 is regarded as a key member of inflammasome sensors (including NLRP1/3/4, AIM2 and pyrin), which could assemble canonical inflammasomes (formed by NOD-like receptors, Caspase-1 and ASC), leading to the maturation and release of IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Our data have found the expression of PRGs and proteins was significantly upregulated in patients with rosacea, and the scores of the activity of pyroptosis pathways were also increased in GSEA and GSVA analysis (Figure 2). In this study, we have mainly focused on NLRP3/Caspase‐1/IL‐1β/GSDMD signalling (the canonical pyroptosis pathway), that our group has been devoted to the exploration for years 20,29–31 . Constantly, existing studies have initially found the role of NLRP3 in the development and progression of rosacea 32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR was performed as described in our previously published study [ 56 ]. The total RNA of cells or tissues were isolated and reversed to cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described in our previously published study [ 56 ]. The total protein of cells was extracted and separated on a 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis and then transferred to nitrocellulose membranes with a transfer apparatus (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%